Effects of fatty acid profile of supplements on intake, performance, carcass traits, meat characteristics, and meat sensorial analysis of feedlot Bos indicus bulls offered a high-concentrate diet. Issue 3 (5th August 2020) - Costa, Carolina; Rizzieri, Ramon; Melo, Gabriel; Müller, Leonardo; Estevan, Daniela; Pacheco, Rodrigo; Millen, Danilo; Pereira, Angélica; Zanatta, Mariana; Cappellozza, Bruno; Cervieri, Rafael; Martins, Cyntia; et al.
Abstract: This experiment was designed to evaluate the effects of lipid source and fatty acid (FA) profile on intake, performance, carcass characteristics, expression of enzymes, and sensorial analysis of Bos indicus animals offered a high-concentrate diet. On day 0, 96 noncastrated animals were blocked by initial body weight (400 ± 19.3 kg), randomly allocated to 1 of 24 pens (4 animals/pen), and pens were randomly assigned to receive: 1) control: basal diet composed of whole cottonseed and corn germ as lipid substrates (CONT; n = 6), 2) calcium salts of fatty acids (CSFA) of soybean: CSFA of soybean oil as replacement for whole cottonseed and corn germ (calcium salts of soybean oil [CSSO]; n = 6), 3) CSFA-Blend: CSFA of palm, cottonseed, and soybean oil as replacement for whole cottonseed and corn germ (calcium salts of vegetable oils [CSVO]; n = 6), and 4) Mix: basal diet containing whole cottonseed, corn germ, and CSVO (MIXT; n = 6). Experiment lasted 108 d and performance, ultrasound measurements, as well as carcass characteristics were evaluated. Additionally, meat FA profile, expression of enzymes involved in lipid metabolism, and sensorial analysis were evaluated. No treatment effects were observed on performance variables, ultrasound, and carcass traits ( P ≥ 0.22), whereas animals receiving CONT had a greater intake of C10:0, C16:0, C16:1 trans -9, C18:1 cis -9, C18:2, C18:3, total FA, monounsatured FA (MUFA), and polyunsaturated FA (PUFA) vs. CSSO and MIXT ( P < 0.05). Conversely, intake ratios of saturated FA (SFA):MUFA and SFA:PUFA were all reduced for CONT vs. other treatments. Meat obtained from CONT animals had greater colorimetric (L*, a*, and b*) values vs. MIXT ( P < 0.01). On meat FA profile, CONT increased C18:0 vs. supplementation with calcium salts ( P < 0.02) and supplementation with CSSO yielded greater meat concentrations of C18:1 trans -10 and C18:2 CLA intermediates ( P < 0.01). Expression of SREBP-1, SCD, and LPL was downregulated for CSSO ( P < 0.05). For sensorial analysis, regular flavor was greater ( P = 0.01) for CSSO vs. other treatments, but also greater aroma ( P = 0.05) vs. CONT and CSVO. In summary, addition of different lipid sources with varying FA profiles into high-concentrate diets did not affect performance and carcass characteristics of B. indicus animals, but supplementation with calcium salts of soybean oil inhibited the mRNA expression of enzymes involved in lipid metabolism, whereas flavor and aroma were positively affected by this lipid source.